Classification of Chinese herbs based on the cluster analysis of delayed luminescence. (3rd August 2015) - Pang, Jingxiang; Yang, Meina; Fu, Jialei; Zhao, Xiaolei; van Wijk, Eduard; Wang, Mei; Liu, Yanli; Zhou, Xiaoyan; Fan, Hua; Han, Jinxiang
Abstract: Traditional Chinese material medica are an important component of the Chinese pharmacopeia. According to the traditional Chinese medicinal concept, Chinese herbal medicines are classified into different categories based on their therapeutic effects, however, the bioactive principles cannot be solely explained by chemical analysis. The aim of this study is to classify different Chinese herbs based on their therapeutic effects by using delayed luminescence (DL). The DL of 56 Chinese herbs was measured using an ultra‐sensitive luminescence detection system. The different DL parameters were used to classify Chinese herbs according to a hierarchical cluster analysis. The samples were divided into two groups based on their DL kinetic parameters. Interestingly, the DL classification results were quite consistent with classification according to the Chinese medicinal concepts of 'cold' and 'heat' properties. In this paper, we show for the first time that by using DL technology, it is possible to classify Chinese herbs according to the Chinese medicinal concept and it may even be possible to predict their therapeutic properties. Copyright © 2015 John Wiley & Sons, Ltd.